Maternal-neonatal care with an ancestral approach - Liliana Alexandra Ríos García; Angélica Salomé Herrera Molina; Viviana del Rocío Mera Herrera; Mayra Carola León Insuasty; Yuleydi Alcaide Guardado; Jacobo Cambil Martín (Medisur)
Foundation: Maternal-neonatal care with an ancestral approach is a practice that integrates ancestral knowledge and practices. Objective: to determine the knowledge in maternal-neonatal care of midwives. Methods: descriptive and cross-sectional study from June to December 2022, in Health District 06D04 Colta Guamote - Guano Penipe, Ecuador. The population was made up of 65 midwives and the sample 34 midwives. Sociodemographic variables and others related to knowledge about care for pregnant women, childbirth and the newborn were studied. Results: 74 % have attended between 10 and 49 births at home and the same percentage reported having kits for childbirth care. The vast majority recommend that pregnant women have four or more check-ups, and consider vaginal bleeding, headache, swelling of hands and feet, and intense abdominal pain as the main symptoms that endanger pregnancy. 82% consider the kneeling position as the main position for childbirth care, and more than a third said that the placenta is planted in the field. Regarding newborn care, the highest percentages recognized: cutting the umbilical cord, direct skin-to-skin contact, and keeping the newborn warm. Among the danger signs for the newborn, 100% indicated not breathing, and more than 70% bathe the newborn between the 1st and 5th day. Conclusions: In indigenous communities, the role of midwives as caregivers is essential